Comparative efficacy of Escherichia coli lipopolysaccharide, oyster glycogen and enrofloxacin on uterine defense mechanism and fertility in crossbred cows with endometritis - PRASAD, J K; SAXENA, M S; PRASAD, SHIV; SINGH, G K (The Indian Journal of Animal Sciences, 2011)
Cows (48) tested positive for endometritis on the basis of appearance of cervical mucus and white side test were randomly divided into 4 groups with 12 cows in each group. In group A, 100 Î¼g of Escherichia coli LPS once, in group B, 500 mg OG once, in group C, enrofloxacin was infused intrauterine for 3 consecutive days and in group D, 20 ml PBS was infused once which served as control group. Endometrial biopsy was collected at 0 h and 72 h from all the cows for histopathological study. Uterine flushing was collected at estrus prior to infusion of drug (0 h) and at 24, 48 and 72 h post treatment for evaluation of changes in total protein concentration, TLC, PMNs%, and the total immunoglobulin concentration. The E. coli LPS and OG treatment significantly increased (P<0.05 or P<0.01) the total protein concentration, TLC, PMNs% and the concentration of total immunoglobulin at 24, 48 and 72 h post treatment. However, intrauterine enrofloxacin therapy reduced (P<0.01) the total protein concentration and PMNs% at 72 h post treatment than pretreatment levels. It is concluded that E. coli LPS and OG may show better therapeutic efficacy to stimulate non-specific uterine defense mechanisms in crossbred cows suffering from endometritis. Further, E. coli LPS and OG may show better therapeutic efficacy than intrauterine enrofloxacin in curing the endometritis in crossbred cows. Â